Dichloroacetate Ameliorates Cardiac Dysfunction Caused by Ischemic Insults Through AMPK Signal Pathway—Not Only Shifts Metabolism. (29th October 2018) - Li, Xuan; Liu, Jia; Hu, Haiyan; Lu, Shaoxin; Lu, Qingguo; Quan, Nanhu; Rousselle, Thomas; Patel, Mulchand S; Li, Ji
Abstract: Dichloroacetate (DCA), an inhibitor of pyruvate dehydrogenase kinase (PDK), regulates substrate metabolism in the heart. AMP-activated protein kinase (AMPK) is an age-related energy sensor that protects the heart from ischemic injury. This study aims to investigate whether DCA can protect the heart from ischemic injury through the AMPK signaling pathway. Young (3–4 months) and aged (20–24 months) male C57BL/6J mice were subjected to ligation of the left anterior descending coronary artery (LAD) for an in vivo ischemic model. The systolic function of the hearts was significantly decreased in both young and aged mice after 45 min of ischemia and 24 h of reperfusion. DCA treatment significantly improved cardiac function in both young and aged mice. The myocardial infarction analysis demonstrated that DCA treatment significantly reduced the infarction size caused by ischemia/reperfusion (I/R) in both young and aged mice. The isolated-cardiomyocyte experiments showed that DCA treatment ameliorated contractile dysfunction and improved the intracellular calcium signal of cardiomyocytes under hypoxia/reoxygenation (H/R) conditions. These cardioprotective functions of DCA can be attenuated by inhibiting AMPK activation. Furthermore, the metabolic measurements with an ex vivo working heart system demonstrated that the effects of DCA treatment on modulating the metabolic shift response to ischemia and reperfusion stress can be attenuated by inhibiting AMPK activity. The immunoblotting results showed that DCA treatment triggered cardiac AMPK signaling pathway by increasing the phosphorylation of AMPK's upstream kinase liver kinase B1 (LKB1) under both sham operations and I/R conditions. Thus, except from modulating metabolism in hearts, the cardioprotective function of DCA during I/R was mediated by the LKB1-AMPK pathway.